Evaluation of intraocular pressure in association with cardiovascular parameters in normocapnic dogs anesthetized with sevoflurane and desflurane - Almeida, D. E.; Rezende, M. L.; Nunes, N.; Laus, J. L. (Blackwell Publishing, 2004)
The objective of this study was to determine intraocular pressure (IOP) and cardiac changes in normocapnic dogs maintained under controlled ventilation and anesthetized using sevoflurane or desflurane. Sixteen healthy adult mixed-breed dogs, seven males and nine females, weighing 10-15 kg were used. The dogs were randomly assigned to one of two groups composed of eight animals anesthetized with sevoflurane (SEVO) or desflurane (DESF). In both groups, anesthesia was induced with propofol (10 mg/kg), and neuromuscular blockade was achieved with rocuronium (0.6 mg/kg/h IV). No premedication was given. Ventilation was adjusted to maintain end-tidal carbon dioxide partial pressure at 35 mmHg. Anesthesia was maintained with 1.5 minimum alveolar concentration (MAC) of sevoflurane or desflurane. In both groups IOP was measured by applanation tonometry (Tono-Pen) before induction of anesthesia. IOP, mean arterial pressure (MAP), heart rate (HR), cardiac index (CI) and central venous pressure (CVP) were also measured 45 min after the beginning of inhalant anesthesia and then every 20 min for 60 min. A one-way repeated measures ANOVA was used to compare data within the same group and Student's t-test was used to assess differences between groups. P < 0.05 was considered statistically significant. Measurements showed normal IOP values in both groups, even though IOP increased significantly from baseline during the use of desflurane. IOP did not differ between groups. CI in the desflurane group was significantly greater than in the sevoflurane group. Sevoflurane and desflurane have no clinically significant effects on IOP, MAP, HR, CI or VCP in the dog.
Keywords: anesthesia; desflurane; intraocular pressure; sevoflurane